Rethinking the expert: Co‐creating curriculum to support international work‐integrated learning with community development organisations. (15th July 2018) - Hammersley, Laura; Lloyd, Kate; Bilous, Rebecca
Abstract : Increasing numbers of Australian students are travelling overseas to undertake short‐term work‐integrated learning placements with community development organisations. In light of recent criticisms emerging in academic and public commentary on short‐term international volunteering, this paper highlights the need for a support curriculum that caters for students from diverse discipline backgrounds, often with little or no previous understanding of community development principles or intercultural engagement. In doing so, we question who is best placed to develop an appropriate curriculum and what might it look like. We draw on Macquarie University's Professional and Community Engagement community development programme to critically reflect on the importance of engaging with diverse knowledge frameworks, approaches to learning and subject expertise of our international community partners. In particular, this paper showcases a community‐based development module co‐created with community partners that aims to encourage students to rethink western‐dominated understandings of development, poverty and inequality. To conclude, we explore how co‐creating curriculum with community partners unsettles assumptions of the university as the only site of expert knowledge and knowledge‐making practices, and reflect on the challenges encountered as we try to contribute to the development of socially and environmentally conscious students.